Histopathological effects of endosulfan to hepatopancreas, gills and ovary of the freshwater crab Zilchiopsis collastinensis (Decapoda: Trichodactylidae) - Negro, Carlos Leandro (2015)
In this work, the effects of a pulse exposure of endosulfan on hepatopancreas, gills and ovary of the burrowing crab Zilchiopsis collastinensis were evaluated. The crabs were exposed to three sublethal concentrations in a pulse system with controlled dilutions. Water samples for pesticide concentrations measurements and crab tissue samples were taken when applications were made and 2, 8, 15 and 22 days after administering the pesticide. The exposure to endosulfan caused an increase in B cell number and a decrease in F and R cell number (p<0.05). Necrotic tubules, abnormal lumen and other histopathologies were observed in the hepatopancreas of crabs exposed to endosulfan. There was an increase in the proportion of collapsed gills caused by endosulfan effects. Other effects as hyperplasia were also observed. There were no changes in the gonadosomatic index of exposed crabs; however there were changes in the volume of oocytes of exposed crabs in certain days (p<0.05). The increase in B cell number and the consequent reduction in F cell number may be related to the detoxification processes. The changes in cell number within the hepatopancreas and the histopathologies observed both in hepatopancreas and gills might be used as endosulfan exposure indicators.